2015
DOI: 10.1007/s10796-015-9564-3
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent approach to data extraction and task identification for process mining

Abstract: Business process mining has received increasing attention in recent years due to its ability to provide process insights by analyzing event logs generated by various enterprise information systems. A key challenge in business process mining projects is extracting process related data from massive event log databases, which requires rich domain knowledge and advanced database skills and could be very labor-intensive and overwhelming. In this paper, we propose an intelligent approach to data extraction and task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In honour of Professor Robert Ayres' contributions to research in technological forecasting and social change, we hope that this study can serve as a useful reference point for researchers in management fields to advance big data research, forecasting and applications of BDA. Analytics technique Liao et al (2014) Analytics technique Yang and Lee (2008) Image semantics Video data Zhang et al (2014) Social influence Mobile Mobile sensing Andrews et al 2016Mobile advertising Fong et al (2015) Mobile targeting Mobile Internet usage Lee (2007) Personalization Li and Du (2012) Mobile advertising Li and Wang (2015) Food supply chain Luo et al (2014) Mobile targeting Recommendation Mobile network Chung et al (2015) Personalization Ghose and Han (2011) Mobile Internet usage Market dynamics Mobile app Ghose and Han (2014) Mobile apps demand Xu et al (2014) Online media He 2013bCase-based reasoning Text mining and Web 2.0 tools can be beneficial to CBR systems with a better user experience. Hu et al (2012) Online reviews Manipulation by firms is found in online reviews, particularly in product ratings.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 99%
“…In honour of Professor Robert Ayres' contributions to research in technological forecasting and social change, we hope that this study can serve as a useful reference point for researchers in management fields to advance big data research, forecasting and applications of BDA. Analytics technique Liao et al (2014) Analytics technique Yang and Lee (2008) Image semantics Video data Zhang et al (2014) Social influence Mobile Mobile sensing Andrews et al 2016Mobile advertising Fong et al (2015) Mobile targeting Mobile Internet usage Lee (2007) Personalization Li and Du (2012) Mobile advertising Li and Wang (2015) Food supply chain Luo et al (2014) Mobile targeting Recommendation Mobile network Chung et al (2015) Personalization Ghose and Han (2011) Mobile Internet usage Market dynamics Mobile app Ghose and Han (2014) Mobile apps demand Xu et al (2014) Online media He 2013bCase-based reasoning Text mining and Web 2.0 tools can be beneficial to CBR systems with a better user experience. Hu et al (2012) Online reviews Manipulation by firms is found in online reviews, particularly in product ratings.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 99%
“…On the one hand, the challenges related to the semantics can be resolved with the help of experts who are directly involved in product development. On the other hand, the challenges related to the event log extraction from a database can be met by extending different approaches ( [6], [7], [8], [9], [10], [11]). However, there is still not a generic solution which can be applied to any kind of database which has no redo logs or just reflecting the current state of the data.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we assume that process related data is available. In (Li et al 2015), the authors have proposed an intelligent approach for extracting this data. Utilizing all of the redundant records in all steps of extracting common fragments is not efficient.…”
Section: Preprocessingmentioning
confidence: 99%